2014
DOI: 10.4172/2167-1222.1000249
|View full text |Cite
|
Sign up to set email alerts
|

Solubility, pH Changes and Releasing Elements of Different Bioceramic and Mineral Trioxide Aggregate Root Canal Sealers Comparative Study

Abstract: Introduction: Bioceramic technology has been introduced recently in endodontics to benefit from the formation of hydroxyapatite during the setting reaction in the presence of tissue fluid and establish a chemical bond at the dentin interface. Objectives: To evaluate some of physiochemical properties of new different Bioceramic (iRoot-SP, EndoSequence, Smartpastebio) versus mineral trioxide aggregate (MTA-Fillapex) root canal sealers. Adseal and ActiV-GP sealers were used as control. Methods: Standard discs (10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 24 publications
(40 reference statements)
0
13
1
Order By: Relevance
“…Most of them have long setting times. According to earlier studies, the high solubility exceeds the allowable threshold (3% mass fraction) 11 , 14 , 15 , 16 , 17 , 18 , 19 that the ISO recommends. 20 Recently, a new chipping bioceramic-based sealer called Cerafill (Prevest DenPro) was introduced.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most of them have long setting times. According to earlier studies, the high solubility exceeds the allowable threshold (3% mass fraction) 11 , 14 , 15 , 16 , 17 , 18 , 19 that the ISO recommends. 20 Recently, a new chipping bioceramic-based sealer called Cerafill (Prevest DenPro) was introduced.…”
Section: Introductionmentioning
confidence: 99%
“… 7 In several studies, it turned out to be biocompatible and nontoxic, 4 and it boosted osteogenesis. 6 , 8 , 9 It also encourages the production of an alkaline pH medium, 10 , 11 which is critical for both bioactivity and antibacterial properties. However, it possesses a prolonged setting time and great solubility when immersed in water.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is seen as an essential consequence because calcium hydroxide, formed by the hydration of calcium silicate cements, dissociates into calcium and hydroxyl ions, which help in stem cell osteogenesis. A pH above 8 can also cause osteoblasts to produce alkaline phosphatase, a hallmark of active calci ed tissue 49 . Calcium silicate material excretes calcium and silicate ions into the environment, promoting cell differentiation and osteogenic gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…The difference between the results of ADT and DCT might be attributed to the different setting times and different flowability of the cement, as AH26 has a longer setting time (9-15h according to the manufacturer) and higher flowability [ 22 ] compared to Adseal (45 mins according to the manufacturer). High phosphorus release by Adseal as demonstrated by Abu Zeid et al [ 23 ] can be responsible for its antibacterial effect as shown by DCT. It has also been shown by Lorencová et al [ 24 ] that phosphorus release from materials could exert antibacterial effects on gram-positive in vitro.…”
Section: Discussionmentioning
confidence: 99%